P-138 Helicobacter Bilis Infection Alters Mucosal Bacteria in Defined Microbiota Mice. (March 2016) - Atherly, Todd; Moser, Curtis; Hostetter, Jesse; Wang, Chong; Proctor, Alexandra; Phillips, Gregory; Brand, Meghan Wymore; Wannemuehler, Michael; Jergens, Albert
Abstract : Background: Strong evidence exists for an important role of the commensal gut bacteria in IBD pathogenesis since changes in microbial composition are often reported in humans and animals. We have previously used Helicobacter bilis infection in defined microbiota C3H/HeN mice, harboring the altered Schaedler flora (ASF), to investigate microbial modulation of IBD. While H. bilis triggers progressive immune responsiveness to commensal ASF bacteria, changes in composition and structure of the mucosal microbiota that contribute to Helicobacter-induced colitis have not been systematically evaluated. The study aims were to investigate temporal alterations in community structure of a defined (ASF-colonized) microbiota in normal and inflamed murine intestines, and to correlate microbiota changes to histologic lesions of colitis. Methods: Two groups of mice were studied: control and H. bilis-colonized mice. Adult ASF mice were colonized with H. bilis by oral gavage then euthanized on weeks 0, 3, 6, and 12 following H. bilis colonization. Proximal colonic tissues containing luminal contents were collected at necropsy for histopathologic (H&E) and fluorescence in situ hybridization (FISH) studies. The mucosal microbiota of colonic tissues was investigated by FISH targeting the 16S rRNA genes of total bacteria, group-specific organisms, and individual ASF bacterial species. The probe array consisted of Eub338 (all bacteria), Erec482 (ASF356/492/500/502), Lab158 (ASF360/361), 457(ASF457), Bac303 (ASF519), and Hel717 (Helicobacter spp.). Sequencing for ASF and H. bilis microbial abundance was performed on cecal contents. Results: H. bilis-colonized ASF mice developed mild-to-moderate typhlocolitis, which peaked 3 to 5 weeks after bacterial colonization. The mucosal microbiota (EUB338) in the proximal colon of healthy mice was most abundant in the free mucus and interlaced compartments. Attaching and invasive ASF bacteria were sparse. In H. bilis-colonized mice, total numbers of colonic EUB-, BAC-, and HEL717-positive bacteria were increased ( P < 0.05) while LAB-positive bacteria were decreased ( P < 0.05) versus control mice. These differences were greatest early in the disease course (ie, 3 and 6 week H. bilis infected mice) for EUB-, LAB-, and HEL717-positive bacteria, with P < 0.05 for each probe. The spatial distribution of mucosal bacteria in colitic mice was significantly ( P < 0.05) different from healthy mice, with increased numbers of bacteria hybridizing against probes EUB, BAC, and HEL717 observed in the free mucus/interlaced layer versus other mucosal compartments. Adherent biofilms in colitic mice were most often ( P < 0.05) composed of bacteria hybridizing against probes EUB, ASF457, and HEL717. In some instances, the biofilm was accompanied by the same bacteria found within the mucosa, including EUB and HEL717 probes ( P < 0.05 for both). Analysis of the cecal microbiota showed no significant differences in relative abundance of ASF members over the 12-week study period. Conclusions: Results indicate that oral inoculation with H. bilis caused major changes in the colonic mucosal microbiota of defined microbiota (ASF-colonized) C3H mice compared with un-inoculated ASF-colonized mice. Altered community structure with murine colitis is characterized by distinct commensal ASF bacterial members that interact with the colonic mucosa, either by formation of an isolating interlaced layer, by attachment, or by invasion, and this interaction is differentially expressed over time.